Re-envisioning Cyprus - Stylianou-Lambert, Theopisti; Antoniou, Lucas; Couta, Melita; Diehl, Johanna; Kyriacou, Phanos (My University, 2010)
Artists and academics join forces in a common effort to “re-envision” Cyprus. The result is anedited volume and a photography & multimedia exhibition. The authors of “Re-envisioning Cyprus” come from different disciplines – such asanthropology, social sciences, art history, literature, cultural theory and visual arts. They usevarious methods – some excavate past images, and some produce or comment on newones. They exploit all kinds of materials – such as press, studio or vernacular photos, statues,landmarks, urban constructions and religious spaces. What united them is first their wish tosee Cyprus with their own eyes and with their own minds, rather than through officialisinglenses, or narratives. Second, they are rather interested in photography, and how it can helpour conceptual understanding of the island. The images each author has selected or produced will be included in the accompaniedexhibition. The exhibition will feature the work of visual artists from Cyprus and abroad andwill be opened by the Minister of Education and Culture, Mr. Andreas Demetriou onWednesday, December 8th at 8pm. Participating Authors and Artists: Loucas Antoniou, Melita Couta, Johanna Diehl, AnandanaKapur, Phanos Kyriacou, Orestis Lambrou, Chrystalleni Loizidou, Peter Loizos, MiriamPaeslack, Haris Pellapaisiotis, Nicos Phillipou, Sondra Sainsbury, Stefanos Stefanides,Theopisti Stylianou-Lambert, Constantinos Taliotis, Demetris Taliotis and Ellene Tsangarides. The exhibition is organized by the University of Nicosia (organizer) and the Cyprus Universityof Technology (partner) and is part of the celebration of the 50th year anniversary of Cyprus.The book is published by the University of Nicosia Press and will be available at theexhibition opening. Editors/ Curators:Peter Loizos (London School of Economics)Nicos Philippou (University of Nicosia)Theopisti Stylianou-Lambert (Cyprus University of Technology)
Keywords: Photography; Multimedia; Cyprus; Visual arts